2011
DOI: 10.1097/olq.0b013e31820ef796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Online Partner Notification Program

Abstract: Our data did not support the effectiveness of the inSPOT intervention among a predominantly heterosexual population in a large urban STI clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 10 publications
0
29
1
Order By: Relevance
“…The circumstances of our trial, in which DIS advised persons with STDs about inSPOT, were different from how most people probably find out about the internet site, and consequently may not accurately reflect the site's real world effect. However, our findings, like another recent report, 13 highlight the limitations of what we know about inSPOT and other similar sites, as well as our uncertainty about whether inSPOT has a positive, negative, or no effect on partner treatment and STI control.…”
Section: Discussioncontrasting
confidence: 52%
“…The circumstances of our trial, in which DIS advised persons with STDs about inSPOT, were different from how most people probably find out about the internet site, and consequently may not accurately reflect the site's real world effect. However, our findings, like another recent report, 13 highlight the limitations of what we know about inSPOT and other similar sites, as well as our uncertainty about whether inSPOT has a positive, negative, or no effect on partner treatment and STI control.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study, availability of a website that could deliver anonymous notification messages was expected to significantly increase notification among men who would not expect to inform their partners under existing conditions (31). In contrast, previous studies from the U.S. assessing public awareness and actual use of internet PN sites among community-based samples of MSM, as well as male and female visitors to STI clinics, found low levels of penetration into these target populations (32,33). The only RCT data on the effectiveness of web-based PN among MSM comes from an incomplete study in Seattle, Washington that found poor uptake and low levels of acceptability among potential recipients of web-based notification messages (34).…”
Section: Introductionmentioning
confidence: 53%
“…About relationships, transient consensual sexual encounters among partners whose expectations for future contact are low or undefined may lend themselves to a brief and even relatively impersonal notification through a popular and accessible medium (eg, email or instant messaging). More established relationships, as alluded to in Rietmeijer et al, 4 perhaps require more personalized and interactive contact. This broad categorization of relationships may be correlated with sexual orientation or gender, which would then be markers for notification preferences.…”
mentioning
confidence: 98%
“…In this editorial, we address a study in which an STD clinic implemented and evaluated the effects of an online partner notification program. 4 The results have led us to write about the role of the intervention, as well as the role of the clinic.If people can find partners online, many of them should be able to either put a disease intervention specialist (DIS) in touch with those partners through the same medium or send an online notification message themselves. In fact, DIS have used email and other electronic methods 5 to contact partners of persons infected with syphilis or HIV, whether the infection occurred with a partner met over the internet.…”
mentioning
confidence: 99%
See 1 more Smart Citation